Interpersonal mistreatments and job outcomes : the roles of stress as mediator and social support as moderator in Pakistan banking sector - Farooq Anwar (2017)
Interpersonal Mistreatment has drawn an unprecedented attention of researchers especially over last couple of decades. Mistreatment at workplace could take different forms, such as abusive supervision, bullying, incivility and social undermining. Nevertheless, previous researches highlight the importance of mistreatment and can be seen exploring its multifaceted dimensions and its relationships with numerous other variables. Yet the scope of current study is to investigate the detrimental effects of this mistreatment upon work outcomes of employees highlighting the mediation mechanism of stress and moderation of social support. The current study therefore, addresses the issue of interpersonal mistreatment and its possible consequences on employees. A sample of 529 usable responses was used for final analysis from total population i.e. employees working in Banking Sector of Pakistan. The scale was developed using adopted valid questionnaires to address the issue of validity in this cross-sectional study. The response rate for return was found to be around 34%. Analyses were done using SPSS and Smart PLS 2 by constructing measurement and structural models. The results revealed that all four forms of mistreatments lead towards a stress at workplace among employees ultimately affecting their job outcomes hence proving the mediation mechanism among variables. Social support, was found to have a significant impact as a moderator mitigating the gravity of the stress caused by mistreatments and their adverse consequences on the various job outcomes. The study has not only served to bridge the gap in literature of mistreatments but also provided a deep insight to the managers, practitioners and policy makers in banking sector of Pakistan in better comprehension of the mechanism and its consequences.